An ultra-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component

By introducing antioxidant powder and ceramic particles into carbon fiber reinforced ceramic matrix composites and combining them with in-situ generated nanowires, a multifunctional carbon fiber reinforced ceramic matrix composite plate component with gradient changes was prepared. This solved the problems of high-temperature oxidation and insufficient mechanical properties of the material, and achieved self-healing and toughening effects.

CN116589296BActive Publication Date: 2025-01-10BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310574505.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-01-10
Estimated Expiration
2043-05-22
Patent Text Reader

Abstract

A super-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component, the preparation method comprises the following steps: preparing a PyC / SiBN anti-oxidation double-layer interface on the fiber cloth surface, introducing SiC nanowires, B4C, Al2O3, ZrSi2, CeO2 and liquid ceramic precursors into the fiber cloth layer respectively, laying SiC nanowires, B4C, Al2O3 between the cloth layers in a manner of gradually increasing from the outer surface to the inner surface, and ZrSi2 and CeO2 in a manner of gradually decreasing from the outer surface to the inner surface, forming a composite material under high temperature and high pressure conditions, and machining the densified semi-finished product to the designed size of the component. The flat plate component prepared by the preparation method of the present invention can withstand high temperatures of 1600°C and above, and effectively solves the problem of poor anti-oxidation performance of carbon fiber, greatly shortens the preparation cycle, and multi-stage toughening enables the ceramic matrix composite flat plate component to have excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a carbon fiber reinforced ceramic matrix composite material flat plate component. Background Art

[0002] In the future, the temperature of the hot end components of the new generation of aerospace engines will reach 1600℃ and above. Almost all the ceramic fibers currently used will fail seriously at this temperature. Carbon fiber is a high-strength and high-modulus high-temperature resistant fiber. Under an inert atmosphere, its mechanical properties such as strength and modulus will not decrease even if the temperature exceeds 2000℃. As the only continuous fiber that can withstand long-term use at temperatures of 1600℃ and above, the continuous carbon fiber reinforced ceramic matrix composites prepared using it have the advantages of low density, ultra-high temperature resistance, corrosion resistance, low thermal expansion coefficient, high thermal conductivity, high vaporization temperature and excellent mechanical properties. As a short-time anti-ablation material, it has been widely used in the aerospace field.

[0003] However, in an aerobic environment with high-pressure, high-speed gas flow erosion, carbon fiber oxidation will occur when the temperature exceeds 400°C, resulting in material failure. Therefore, carbon fiber reinforced ceramic matrix composites are used as high-temperature structural materials in aerospace engines that are reusable, have a wide temperature range, and are in complex heat / force / oxygen coupling service environments. However, there is still a bottleneck problem of easy oxidation of fibers. At present, the problem of easy oxidation of carbon fiber reinforced ceramic matrix composites is mainly solved by preparing anti-oxidation coatings. However, during service, the coatings are very easy to peel off, and after peeling off, they will no longer have a protective effect. Existing coating technology alone cannot achieve long-term ultra-high temperature thermal protection in a wide temperature range. Ceramic particles with good anti-oxidation and heat insulation effects in different temperature ranges are added to the material to modify the matrix. Through component regulation, the composite material can be guaranteed to have a longer service life, realize self-healing in a wide temperature range and ultra-high temperature insulation and anti-oxidation, and improve the anti-oxidation and self-healing ability of carbon fiber reinforced ceramic matrix composites. At the same time, during service, the engine also needs to withstand complex and harsh thermal-mechanical loads. In order to further improve the mechanical properties of the composite material, multi-scale toughening of the material can be achieved by in-situ generation of nanowires. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a super-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component, improve the oxidation resistance of the carbon fiber reinforced ceramic matrix composite material, and prepare a flat plate component with good self-healing performance.

[0005] To achieve the above-mentioned purpose, the technical solution provided by the present invention is as follows: In the first aspect, the present invention provides a super-high temperature resistant self-healing multifunctional gradient-gradient carbon fiber reinforced ceramic-based composite flat plate component, comprising the following steps: S1: determining the number of fiber cloth layers according to the size of the flat plate component, and preparing a PyC / SiBN antioxidant double-layer interface phase on the surface of the fiber cloth; the fiber cloth is a two-dimensional satin cloth woven from carbon fiber; S2: dividing the fiber cloth into four parts A, B, C, and D according to 1 / 3, 1 / 6, 1 / 6, and 1 / 3 of the total number of cloth layers, introducing ZrSi2 and CeO2 powders into the fiber cloth in part A, introducing Al2O3, ZrSi2 and CeO2 powders into the fiber cloth in part B, introducing B4C, Al2O3 and ZrSi2 powders into the fiber cloth in part C, introducing B4C and Al2O3 powders into the fiber cloth in part D, mixing a ferrocene catalyst into a liquid ceramic precursor, and introducing it into each layer of fiber cloth. S3: The SiC nanowires, B4C, and Al2O3 between the layers are gradually increased from the outer surface to the inner surface, and the ZrSi2 and CeO2 are gradually decreased from the outer surface to the inner surface. The layering sequence is 1 / 2A–1 / 2B–1 / 2C–D–1 / 2C–1 / 2B–1 / 2A; S4: The composite material is formed under high temperature and high pressure conditions; S5: The densified semi-finished product is machined to the designed size of the component.

[0006] In a further embodiment of the present invention, in step S1, the preparation of the antioxidant double-layer interface phase on the surface of the fiber cloth includes the preparation of the PyC interface phase and the preparation of the SiBN interface phase, wherein the specific method for preparing the PyC interface phase is: using a directional flow chemical vapor deposition process, arranging the fibers in the chemical vapor deposition equipment, first degumming the fibers in the fiber cloth at 800-1200°C, using natural gas and nitrogen as gas precursors, the deposition temperature is 800-1200°C, the deposition time is 2-10h, and the deposition pressure is 900-6000Pa, wherein the natural gas flow rate is 50-150mL / min, and the nitrogen flow rate is 50-150mL / min. The specific method for preparing the SiBN interface phase is: using a directional flow chemical vapor deposition process, the fiber cloth continues to be placed in the deposition equipment, the natural gas and nitrogen gases are turned off, SiCl4, NH3, BCl3, and H2 are used as gas precursors, Ar is used as a carrier gas and a dilution gas, the deposition temperature is 800-1200°C, the deposition time is 2-10h, and the deposition pressure is 1500-3000Pa, wherein the SiCl4 flow rate is 150-500mL / min, the NH3 flow rate is 150-500mL / min, the BCl3 flow rate is 150-500mL / min, the H2 flow rate is 150-500mL / min, and the Ar flow rate is 100-500mL / min.

[0007] In a further embodiment of the present invention, in step S2, the fiber cloth is divided into four parts A, B, C, and D according to 1 / 3, 1 / 6, 1 / 6, and 1 / 3 of the total number of cloth layers, ZrSi2 and CeO2 powders are introduced into the fiber cloth in part A, Al2O3, ZrSi2, and CeO2 powders are introduced into the fiber cloth in part B, B4C, Al2O3, and ZrSi2 powders are introduced into part C, B4C and Al2O3 powders are introduced into part D, a ferrocene catalyst is mixed into the liquid ceramic precursor, and then introduced into the fiber cloth. The slurry is made of powder, dispersant and deionized water. The mass ratio of part A ZrSi2:CeO2:dispersant:deionized water is (5-10):(5-20):(0.5-3):(50-80); the mass ratio of part B Al2O3:ZrSi2:CeO2:dispersant:deionized water is (5-20):(3-8):(1-5):(0.5-3):(50-80); the mass ratio of part C B4C:Al2O3: The mass ratio of ZrSi2: dispersant: deionized water is (5-15): (5-10): (1-5): (0.5-3): (50-80); the mass ratio of part D B4C and Al2O3: dispersant: deionized water is (10-20): (5-10): (0.5-3): (50-80); a liquid ceramic precursor solution mixed with 0.5wt% to 2.5wt% of ferrocene catalyst is introduced into each layer of fiber cloth.

[0008] In a further embodiment of the present invention, in step S3, the order of plying is 1 / 2A–1 / 2B–1 / 2C–D–1 / 2C–1 / 2B–1 / 2A, and a preform is obtained after plying, and the fiber volume content in the preform is 30% to 45%.

[0009] In a further embodiment of the present invention, in step S4, the preform after layering is placed in a high-temperature cracking furnace to first generate SiC nanowires at a growth temperature of 1100-1400°C, and Ar is introduced as a protective atmosphere at a flow rate of 200-500 mL / min. The temperature is kept at 1-3 hours, and then the temperature is continued to rise to 1600-1900°C, the pressure is 15-30 MPa, and the temperature is kept at 1-3 hours.

[0010] In a further embodiment of the present invention, in step S5, the semi-finished product obtained includes the fiber preform, the composite interface layer and the matrix layer from the inside to the outside, and the mechanical processing is only to remove the outermost matrix layer.

[0011] In the second aspect, the present invention provides an ultra-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite material flat plate component prepared according to the above method, which has the advantages of anti-oxidation, good self-healing performance, excellent mechanical properties, etc.

[0012] The excellent effects produced by the preparation process of the present invention are:

[0013] (1) Ceramic fibers, represented by SiC fibers, have poor resistance to ultra-high temperatures (>1600°C). They are prone to fiber failure under high temperature conditions, which can lead to a serious decline in the overall performance of ceramic-based composites. Carbon fibers themselves can withstand temperatures of 3000°C and can still maintain good mechanical properties under ultra-high temperature conditions. They play a good role in strengthening and toughening the composite material, allowing the ceramic-based composite flat plate components to maintain high mechanical strength over a long protection period.

[0014] (2) B4C and Al2O3 powders are introduced into the interior of the composite material to mainly play the role of self-healing. ZrSi2 and CeO2 powders are introduced into the exterior of the composite material to mainly play the role of heat insulation. Different powders are introduced layer by layer through gradient change, so that the composite material has good self-healing effect in a wide temperature range and protects the carbon fiber from oxygen erosion under high temperature conditions.

[0015] (3) While introducing the powder, SiC nanowires are generated in situ inside the composite material to achieve multi-level toughening and further improve the mechanical properties of the composite material. On the other hand, the introduction of SiC nanowires can appropriately alleviate the residual stress generated during the preparation of the composite material due to the mismatch of the thermal expansion coefficients of the fiber and the matrix.

[0016] (4) The composite materials prepared by combining the layered structure with a high temperature and high pressure one-step molding process can not only greatly shorten the preparation cycle of the composite materials and achieve near-net size one-step full densification, but also effectively regulate the composition and structure of the composite materials, achieve a multifunctional gradient gradual wide temperature range self-healing effect, and improve the mechanical properties of the composite materials. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0019] Unless otherwise specified, the test materials used in the following examples were purchased from natural conventional reagent stores.

[0020] The quantitative tests in the following examples were all performed in triplicate, and the data are the average values ​​or the average values ​​± standard deviations of the triplicate tests.

[0021] The present invention provides a method for producing an ultra-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite material flat plate component, comprising the following steps:

[0022] S1: Preparing a PyC / SiBN anti-oxidation double-layer interface phase on the surface of the fiber cloth, wherein the specific method for preparing the PyC interface phase is: using a directional flow chemical vapor deposition process, arranging the fibers in the chemical vapor deposition equipment, first degumming the fibers in the fiber cloth at 800-1200°C, using natural gas and nitrogen as gas precursors, the deposition temperature is 800-1200°C, the deposition time is 2-10h, and the deposition pressure is 900-6000Pa, wherein the natural gas flow rate is 50-150mL / min, and the nitrogen flow rate is 50-150mL / min. The specific method for preparing the SiBN interface phase is: using a directional flow chemical vapor deposition process, the fiber cloth continues to be placed in the deposition equipment, the natural gas and nitrogen gases are turned off, SiCl4, NH3, BCl3, and H2 are used as gas precursors, Ar is used as a carrier gas and a dilution gas, the deposition temperature is 800-1200°C, the deposition time is 2-10h, and the deposition pressure is 1500-3000Pa, wherein the SiCl4 flow rate is 150-500mL / min, the NH3 flow rate is 150-500mL / min, the BCl3 flow rate is 150-500mL / min, the H2 flow rate is 150-500mL / min, and the Ar flow rate is 100-500mL / min.

[0023] S2: Divide the fiber cloth into four parts, namely A, B, C and D, according to 1 / 3, 1 / 6, 1 / 6 and 1 / 3 of the total number of cloth layers. Introduce ZrSi2 and CeO2 powders into the fiber cloth in part A, introduce Al2O3, ZrSi2 and CeO2 powders into the fiber cloth in part B, introduce B4C, Al2O3 and ZrSi2 powders into part C, introduce B4C and Al2O3 powders into part D, mix different proportions of ferrocene catalyst into the liquid ceramic precursor and introduce it into the fiber cloth. The slurry is made of powder, dispersant and deionized water. The mass ratio of ZrSi2:CeO2:dispersant:deionized water in part A is (5-10):(5-20):(0.5-3):(50-80); the mass ratio of Al2O3:ZrSi2:CeO2:dispersant:deionized water in part B is (5-20):(3-8):(1-5):(0.5-3):(50-80); the mass ratio of B4C:Al2O3:ZrSi2:CeO2:dispersant:deionized water in part C is (5-20):(3-8):(1-5):(0.5-3):(50-80); 2O3: ZrSi2: dispersant: deionized water mass ratio is (5-15): (5-10): (1-5): (0.5-3): (50-80); part D B4C and Al2O3: dispersant: deionized water mass ratio is (10-20): (5-10): (0.5-3): (50-80); 0.5wt% to 2.5wt% of ferrocene catalyst is mixed into the liquid ceramic precursor solution respectively.

[0024] S3: The order of plying is 1 / 2A–1 / 2B–1 / 2C–D–1 / 2C–1 / 2B–1 / 2A, and a preform is obtained after plying, wherein the fiber volume content of the preform is 30% to 45%.

[0025] S4: placing the preform after layering in a high-temperature cracking furnace, first generating SiC nanowires, the growth temperature is 1100-1400°C, introducing Ar as a protective atmosphere, the Ar flow rate is 200-500mL / min, keeping warm for 1-3h, then continue to raise the temperature to 1600-1900°C, the pressure is 15-30MPa, and keeping warm for 1-3h.

[0026] S5: Mechanically process the product obtained in step S4 to the designed size of the flat plate component. The mechanical processing is only to remove the matrix layer remaining on the surface of the composite material for easy assembly, and will not cause damage to the fiber layer.

[0027] The method for producing an ultra-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite material flat plate component of the present invention will be further described below in conjunction with specific embodiments.

[0028] Example 1

[0029] The carbon fibers were arranged in a chemical vapor deposition device, and the fibers in the fiber cloth were degummed at 800°C. Natural gas and nitrogen were used as gas precursors, the deposition temperature was 900°C, the deposition time was 5h, and the deposition pressure was 5000Pa, wherein the natural gas flow rate was 50mL / min, and the nitrogen flow rate was 120mL / min. The natural gas and nitrogen were shut down, SiCl4, NH3, BCl3, and H2 were used as gas precursors, Ar was used as a carrier gas and dilution gas, the deposition temperature was 900°C, the deposition time was 8h, and the deposition pressure was 2000Pa, wherein the SiCl4 flow rate was 180mL / min, the NH3 flow rate was 320mL / min, the BCl3 flow rate was 320mL / min, the H2 flow rate was 240mL / min, and the Ar flow rate was 400mL / min. The pressure impregnation process (the specific steps of the pressure impregnation process are to put the fiber cloth into the impregnation tank, evacuate the vacuum, then add the prepared slurry through the feed port, and then introduce argon gas to make the pressure reach 2MPa) is used to introduce ZrSi2 and CeO2 powders into the fiber cloth in part A, and the slurry composition is ZrSi2:CeO2:dispersant:deionized water with a mass ratio of 8:20:2:70; Al2O3, ZrSi2 and CeO2 powders are introduced into the fiber cloth in part B, and the slurry composition is Al2 The mass ratio of O3: ZrSi2: CeO2: dispersant: deionized water is 18: 5: 5: 2: 70; B4C, Al2O3 and ZrSi2 powders are introduced into part C, and the slurry composition is B4C: Al2O3: ZrSi2: dispersant: deionized water in a mass ratio of 15: 10: 5: 2: 68; B4C and Al2O3 powders are introduced into the fiber cloth in part D, and the slurry composition is B4C and Al2O3: dispersant: deionized water in a mass ratio of 18: 10: 2: 70. The impregnated fiber cloth is placed in an oven, and the oven temperature is set to 120°C to remove moisture from the slurry. After drying, a liquid PCS precursor solution mixed with 2wt% ferrocene catalyst is introduced between the fiber cloths by a brushing process. The prepared solution is dipped with a brush and brushed on the fiber cloth. After brushing, the layers are laid in the order of 1 / 2A-1 / 2B-1 / 2C-D-1 / 2C-1 / 2B-1 / 2A. The fiber cloth after laying is placed in an oven, and the oven temperature is set to 120°C to make the PCS solution (polycarbosilane) complete cross-linking and curing. The cured preform is placed in a high-temperature cracking furnace at a temperature of 1100°C, and Ar is introduced as a protective atmosphere with an Ar flow rate of 500mL / min. The temperature is kept for 1h, and then the temperature is continued to rise to 1900°C, the pressure is 28MPa, and the temperature is kept for 3h. After cooling to room temperature, the semi-finished product is taken out and the semi-finished product is mechanically processed to remove the excess substrate layer on the surface to reach the designed size.

[0030] The density of the ceramic matrix composite material plate component obtained in Example 1 is 2.47 g / cm3 The porosity is 1.8%, the flexural strength is 387MPa, the flexural modulus is 83GPa, the weight loss rate after oxidation at 1600℃ for 200h is -0.3%, and the strength retention rate after oxidation at 1600℃ for 200h is 73%.

[0031] Example 2

[0032] The carbon fibers were arranged in a chemical vapor deposition device, and the fibers in the fiber cloth were degummed at 800°C. Natural gas and nitrogen were used as gas precursors, the deposition temperature was 980°C, the deposition time was 3h, and the deposition pressure was 1200Pa, wherein the natural gas flow rate was 80mL / min, and the nitrogen flow rate was 150mL / min. The natural gas and nitrogen were shut down, SiCl4, NH3, BCl3, and H2 were used as gas precursors, Ar was used as a carrier gas and dilution gas, the deposition temperature was 900°C, the deposition time was 10h, and the deposition pressure was 1500Pa, wherein the SiCl4 flow rate was 200mL / min, the NH3 flow rate was 380mL / min, the BCl3 flow rate was 220mL / min, the H2 flow rate was 180mL / min, and the Ar flow rate was 300mL / min. ZrSi2 and CeO2 powders were introduced into the fiber cloth in part A by means of a pressure impregnation process, and the slurry composition was as follows: ZrSi2:CeO2:dispersant:deionized water in a mass ratio of 10:18:2:70; Al2O3, ZrSi2 and CeO2 powders were introduced into the fiber cloth in part B, and the slurry composition was as follows: Al2O3:ZrSi2:CeO2:dispersant:deionized water in a mass ratio of 14:8:5:3:70; B4C, Al2O3 and ZrSi2 powders were introduced into part C, and the slurry composition was as follows: B4C:Al2O3:ZrSi2:dispersant:deionized water in a mass ratio of 13:10:5:2:70; B4C and Al2O3 powders were introduced into the fiber cloth in part D, and the slurry composition was as follows: B4C and Al2O3:dispersant:deionized water in a mass ratio of 20:8:2:70. After drying, a PSNB solution mixed with 2wt% ferrocene catalyst is introduced between the fiber cloths by brushing. After brushing, the layers are laid in the order of 1 / 2A-1 / 2B-1 / 2C-D-1 / 2C-1 / 2B-1 / 2A, and the cured preform is placed in a high-temperature cracking furnace. The PSNB solution is a liquid polyborosilazane precursor, the temperature is 1150°C, Ar is introduced as a protective atmosphere, the Ar flow rate is 350mL / min, and the temperature is kept for 1h, and then the temperature is continued to rise to 1800°C, the pressure is 25MPa, and the temperature is kept for 3h. After cooling to room temperature, the semi-finished product is taken out and the semi-finished product is mechanically processed to remove the excess substrate layer on the surface to reach the designed size.

[0033] The density of the ceramic matrix composite material plate component obtained in Example 2 is 2.43 g / cm3 The porosity is 1.9%, the flexural strength is 483MPa, the flexural modulus is 91GPa, the weight loss rate after oxidation at 1600℃ for 200h is -0.6%, and the strength retention rate after oxidation at 1600℃ for 200h is 87%.

[0034] Example 3

[0035] The carbon fibers were arranged in a chemical vapor deposition device, and the fibers in the fiber cloth were degummed at 800°C. Natural gas and nitrogen were used as gas precursors, the deposition temperature was 1100°C, the deposition time was 3h, and the deposition pressure was 2800Pa, wherein the natural gas flow rate was 100mL / min, and the nitrogen flow rate was 140mL / min. The natural gas and nitrogen were shut down, SiCl4, NH3, BCl3, and H2 were used as gas precursors, Ar was used as a carrier gas and dilution gas, the deposition temperature was 1000°C, the deposition time was 10h, and the deposition pressure was 2500Pa, wherein the SiCl4 flow rate was 400mL / min, the NH3 flow rate was 420mL / min, the BCl3 flow rate was 380mL / min, the H2 flow rate was 420mL / min, and the Ar flow rate was 400mL / min. ZrSi2 and CeO2 powders were introduced into the fiber cloth in part A by means of a pressure impregnation process, and the slurry composition was as follows: ZrSi2:CeO2:dispersant:deionized water in a mass ratio of 8:20:3:69; Al2O3, ZrSi2 and CeO2 powders were introduced into the fiber cloth in part B, and the slurry composition was as follows: Al2O3:ZrSi2:CeO2:dispersant:deionized water in a mass ratio of 20:6:5:3:66; B4C, Al2O3 and ZrSi2 powders were introduced into part C, and the slurry composition was as follows: B4C:Al2O3:ZrSi2:dispersant:deionized water in a mass ratio of 14:8:5:3:70; B4C and Al2O3 powders were introduced into the fiber cloth in part D, and the slurry composition was as follows: B4C and Al2O3:dispersant:deionized water in a mass ratio of 18:9:3:70. After drying, a PSNB solution mixed with 2 wt% ferrocene catalyst was introduced between the fiber cloths by brushing, and the layers were laid in the order of 1 / 2A-1 / 2B-1 / 2C-D-1 / 2C-1 / 2B-1 / 2A. The cured preform was placed in a high-temperature cracking furnace at a temperature of 1300°C, with Ar introduced as a protective atmosphere at an Ar flow rate of 500 mL / min, and kept warm for 1 hour, then continued to heat up to 1900°C, with a pressure of 30 MPa, and kept warm for 3 hours. After cooling to room temperature, the semi-finished product was taken out and the semi-finished product was mechanically processed to remove the excess substrate layer on the surface to reach the designed size.

[0036] The density of the ceramic matrix composite material plate component obtained in Example 3 is 2.39 g / cm 3The porosity is 2.6%, the flexural strength is 405MPa, the flexural modulus is 79GPa, the weight loss rate after oxidation at 1600℃ for 200h is -0.1%, and the strength retention rate after oxidation at 1600℃ for 200h is 68%.

[0037] Comparative Example 1

[0038] The carbon fibers were arranged in a chemical vapor deposition device, and the fibers in the fiber cloth were degummed at 800°C. Natural gas and nitrogen were used as gas precursors, the deposition temperature was 980°C, the deposition time was 3h, and the deposition pressure was 1200Pa, wherein the natural gas flow rate was 80mL / min, and the nitrogen flow rate was 150mL / min. The natural gas and nitrogen were shut down, SiCl4, NH3, BCl3, and H2 were used as gas precursors, Ar was used as a carrier gas and dilution gas, the deposition temperature was 900°C, the deposition time was 10h, and the deposition pressure was 1500Pa, wherein the SiCl4 flow rate was 200mL / min, the NH3 flow rate was 380mL / min, the BCl3 flow rate was 220mL / min, the H2 flow rate was 180mL / min, and the Ar flow rate was 300mL / min. PSNB solution was introduced between the fiber cloths by brushing process. After laying, the cured preform was placed in a high-temperature cracking furnace at 1150℃, with Ar as protective atmosphere at a flow rate of 350mL / min. The temperature was kept for 1h, and then the temperature was continued to rise to 1800℃, the pressure was 25MPa, and the temperature was kept for 3h. After cooling to room temperature, the semi-finished product was taken out and the semi-finished product was mechanically processed to remove the excess substrate layer on the surface to reach the designed size.

[0039] The density of the ceramic matrix composite material plate component obtained in Comparative Example 1 is 2.26 g / cm 3 The porosity is 8.5%, the flexural strength is 423MPa, the flexural modulus is 68GPa, the weight loss rate after oxidation at 1600℃ for 200h is 25.8%, and the strength retention rate after oxidation at 1600℃ for 200h is 47%.

[0040] Comparative Example 2

[0041] The silicon carbide fiber was arranged in a chemical vapor deposition device, and the fiber in the fiber cloth was degummed at 800°C. Natural gas and nitrogen were used as gas precursors, the deposition temperature was 980°C, the deposition time was 3h, and the deposition pressure was 1200Pa, wherein the natural gas flow rate was 80mL / min, and the nitrogen flow rate was 150mL / min. The natural gas and nitrogen were shut down, SiCl4, NH3, BCl3, and H2 were used as gas precursors, Ar was used as carrier gas and dilution gas, the deposition temperature was 900°C, the deposition time was 10h, and the deposition pressure was 1500Pa, wherein the SiCl4 flow rate was 200mL / min, the NH3 flow rate was 380mL / min, the BCl3 flow rate was 220mL / min, the H2 flow rate was 180mL / min, and the Ar flow rate was 300mL / min. ZrSi2 and CeO2 powders were introduced into the fiber cloth in part A by means of a pressure impregnation process, and the slurry composition was as follows: ZrSi2:CeO2:dispersant:deionized water in a mass ratio of 10:18:2:70; Al2O3, ZrSi2 and CeO2 powders were introduced into the fiber cloth in part B, and the slurry composition was as follows: Al2O3:ZrSi2:CeO2:dispersant:deionized water in a mass ratio of 14:8:5:3:70; B4C, Al2O3 and ZrSi2 powders were introduced into part C, and the slurry composition was as follows: B4C:Al2O3:ZrSi2:dispersant:deionized water in a mass ratio of 13:10:5:2:70; B4C and Al2O3 powders were introduced into the fiber cloth in part D, and the slurry composition was as follows: B4C and Al2O3:dispersant:deionized water in a mass ratio of 20:8:2:70. After drying, a PSNB solution mixed with 2 wt% ferrocene catalyst was introduced between the fiber cloths by brushing, and the layers were laid in the order of 1 / 2A-1 / 2B-1 / 2C-D-1 / 2C-1 / 2B-1 / 2A. The cured preform was placed in a high-temperature cracking furnace at a temperature of 1150°C, with Ar introduced as a protective atmosphere at an Ar flow rate of 350 mL / min, and kept warm for 1 hour, then continued to heat up to 1800°C, with a pressure of 25 MPa, and kept warm for 3 hours. After cooling to room temperature, the semi-finished product was taken out and the semi-finished product was mechanically processed to remove the excess substrate layer on the surface to reach the designed size.

[0042] The density of the ceramic matrix composite material plate component obtained in Comparative Example 2 is 2.63 g / cm 3 , porosity is 1.4%, flexural strength is 572MPa, flexural modulus is 102GPa, weight loss after oxidizing at 1600℃ for 200h is -2.4%, and strength retention after oxidizing at 1600℃ for 200h is 28%. In Comparative Example 2, the carbon fiber is replaced with SiC fiber, and the ceramic fiber is severely damaged.

Claims

1. A method for preparing a super-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component, characterized in that: The following steps are involved: S1: Determine the number of fiber cloth layers according to the size of the flat component, and prepare a PyC / SiBN anti-oxidation double-layer interface phase on the surface of the fiber cloth; the fiber cloth is a two-dimensional satin cloth woven from carbon fibers; S2: Divide the fiber cloth into four parts, A, B, C, and D, according to 1 / 3, 1 / 6, 1 / 6, and 1 / 3 of the total number of cloth layers. Introduce ZrSi2 and CeO2 powders into the fiber cloth in part A, Al2O3, ZrSi2, and CeO2 powders into the fiber cloth in part B, B4C, Al2O3, and ZrSi2 powders into the fiber cloth in part C, and B4C and Al2O3 powders into the fiber cloth in part D. The powders are introduced by a pressurized impregnation process. The fiber cloth is placed in an impregnation tank, and the slurry is added from the feed port after vacuuming. Then pressurize until the pressure reaches 2-5MPa, immerse for 2-5h, take out and put the fiber cloth into an oven, set the oven temperature to 80-150°C, remove the moisture in the slurry, and make the powder in the slurry adhere to the fiber cloth; the slurry is made of powder, dispersant, and deionized water; after the fiber cloth is immersed in the slurry and dried, a liquid ceramic precursor solution mixed with different proportions of ferrocene catalyst is introduced into each layer of fiber cloth by brushing, and the liquid ceramic precursor includes a liquid polycarbosilane precursor, a liquid polysilazane precursor or a liquid polyborosilazane precursor; S3: The contents of SiC nanowires, B4C powder, and Al2O3 powder on the fiber cloth gradually increase from the outer surface to the inner surface, and the contents of ZrSi2 powder and CeO2 powder gradually decrease from the outer surface to the inner surface. The order of plying is 1 / 2 A – 1 / 2 B – 1 / 2 C – D – 1 / 2 C – 1 / 2 B – 1 / 2 A. S4: forming a composite material under high temperature and high pressure conditions; placing the preform after layering in a high temperature cracking furnace, first generating SiC nanowires, the growth temperature is 1100-1400°C, introducing Ar as a protective atmosphere, the Ar flow rate is 200-500mL / min, keeping the temperature for 1-3h, and then continuing to increase the temperature to 1600-1900°C, the pressure is 15-30MPa, and keeping the temperature for 1-3h; S5: Machining the densified semi-finished product to the designed size of the component.

2. The method for preparing a super-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component according to claim 1, characterized in that: In the step S2, the mass ratio of ZrSi2:CeO2:dispersant:deionized water in the slurry of the fiber cloth of part A is (5-10):(5-20):(0.5-3):(50-80); the mass ratio of Al2O3:ZrSi2:CeO2:dispersant:deionized water in the slurry of part B fiber cloth is (5-20):(3-8):(1-5):(0.5-3):(50-80); the mass ratio of B4C:Al2O3:ZrSi2:CeO2:dispersant:deionized water in the slurry of part C fiber cloth is (5-20):(3-8):(1-5):(0.5-3):(50-80); The mass ratio of rSi2: dispersant: deionized water is (5~15): (5~10): (1~5): (0.5~3): (50~80); in the slurry of the fiber cloth in part D, the mass ratio of B4C: Al2O3: dispersant: deionized water is (10~20): (5~10): (0.5~3): (50~80); after painting, lay the layers in the order described in S3, and then place them in an oven with the oven temperature set to 120-150°C to allow the precursor to complete cross-linking and curing.

3. The method for preparing a super-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component according to claim 1, characterized in that: After the ply laying in step S3, a preform is obtained, and the fiber volume content in the preform is 30% to 45%.

4. The method for preparing a super-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component according to claim 1, characterized in that: In the step S1, the preparation method of the PyC interface phase is to arrange the fibers in a chemical vapor deposition device by using a directional flow chemical vapor deposition process, first degumming the fibers in the fiber cloth at 800-1200° C., using natural gas and nitrogen as gas precursors, the deposition temperature is 800-1200° C., the deposition time is 2-10 hours, and the deposition pressure is 900-6000 Pa, wherein the natural gas flow rate is 50-150 mL / min, and the nitrogen flow rate is 50-150 mL / min; In the step S1, the preparation method of the SiBN interface phase is to adopt a directional flow chemical vapor deposition process, the fiber cloth continues to be placed in the deposition equipment, the natural gas and nitrogen gases are turned off, SiCl4, NH3, BCl3, H2 are used as gas precursors, Ar is used as a carrier gas and a dilution gas, the deposition temperature is 800-1200°C, the deposition time is 2-10h, and the deposition pressure is 1500-3000Pa, wherein the SiCl4 flow rate is 150-500mL / min, the NH3 flow rate is 150-500mL / min, the BCl3 flow rate is 150-500mL / min, the H2 flow rate is 150-500mL / min, and the Ar flow rate is 100-500mL / min.

5. The method for preparing a super-high temperature resistant self-healing multifunctional gradient carbon fiber reinforced ceramic matrix composite flat plate component according to claim 1, characterized in that: The semi-finished product obtained in step S5 includes the fiber preform, the composite interface layer and the matrix layer from the inside to the outside, and the mechanical processing is only to remove the outermost matrix layer.

6. A ceramic matrix composite flat plate component for aviation prepared by the method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for preparing Cf / ZrC-SiC superhigh-temperature ceramic composite material through hot-pressing sintering / precursor cracking process

    CN104311090A

  • Carbon fiber-reinforced (carbon-) silicon carbide base-ultra-high temperature ceramic base compound material and production method thereof

    CN109970460A